The Quarterly Journal of Economics Volume 128 August 2013 Issue 3 - Front Cover (Quarterly Journal of Economics, 2013)
The Quarterly Journal of Economics Volume 128 August 2013 Issue 3 - Front Cover Get access The Quarterly Journal of Economics, Volume 128, Issue 3, August 2013, Page i1, https://doi.org/10.1093/qje/qjs059 Published: 05 July 2013